Increased antioxidant activity and polyphenol metabolites in methyl jasmonate treated mung bean (Vigna radiata) sprouts - Li LI (Food Science and Technology)
Abstract Mung bean sprouts are a popular health food both in China and worldwide. We determined the optimal concentration of exogenous methyl jasmonate (MeJA) for the promotion of the sprouting in mung beans (Vigna radiata). The 1,1-diphenyl-2- picrylhydrazyl radical (DPPH) scavenging test showed that MeJA application resulted in significantly improved antioxidant capacity in the sprouts 72 h later. Measurement of total polyphenols in MeJA-treated beans from 0 to 168 h, using Folin–Ciocalteu colorimetry, showed that the polyphenols changing was significantly correlated with antioxidant activity. The main polyphenols isovitexin, kaempferol-3-O-rutinoside, daidzein, genistein, isoquercitrin, p-coumaric acid, and caffeic acid were quantified using high-performance liquid chromatography (HPLC/QqQ MS) and partial least squares discriminant analysis (PLS-DA). MeJA promoted the production of polyphenols, metabolites, and antioxidants in the sprouts; therefore, its use may allow sprouts to be prepared more quickly or increase their nutritional value.